PENGARUH LATIHAN INTERVAL RUNNING TERHADAP DAYA TAHAN KARDIOVASKULAR PADA ATLET ABS MARSA - Putri Julia Anisah; Hayati (LPPM Universitas PGRI Adi Buana, 2024)
This research was motivated by movements resulting from the sport of badminton, where athletes perform fast running movements, jumping movements, stretching, long and short strides, stopping suddenly and immediately moving again. In addition, athletes must master several basic techniques such as racket grip, footwork, arm swing, concentration and endurance to achieve the highest possible level of performance. To carry out these activities athletes must have good cardiovascular endurance. To increase cardiovascular endurance, you can do various types of exercise, including interval training. Interval training itself is a type of exercise that can increase a person's heart and lung endurance. From the above background, this study aims to examine the results of cardiovascular endurance in PB ABS MARSA athletes. This research is a quantitative research with a two-group pretest-posttest design where this design contains a pretest and posttest. The sample in this study was PB Abs Marsa athletes, totaling 14 athletes who were divided into an experimental group and a control group. The experimental group was given interval running training treatment for 12 meetings over 3 weeks. The implementation and collection of cardiovascular endurance data in this study used the 2.4 km running test method. After obtaining the results data, the statistical analysis method used was description analysis, normality test, homogeneity test, and t test using SPSS V.29. Based on the data results using SPSS V.29, it is known that the sig. (2-tailed) in the experimental group was 0.001, in the control group it was 0.18, so the sig. (2-tailed) in the experimental group < 0.05, it can be stated that the hypothesis is accepted, so it can be stated that interval running training has an effect on PB ABS MARSA cardiovascular endurance. Keywords: interval training, cardiovaskular endurance, badminton